Guidelines Procurement under IBRD Loans and IDA Credits - World Bank (The World Bank, 2004)
The purpose of these Guidelines is to inform those carrying out a project that is financed in whole or in part by loans from the International Bank for Reconstruction and Development (IBRD) or a credit or grant from the International Development Association (IDA), of the policies that govern the procurement of goods, works, and services (other than consultant services) reqired for the project